2020
DOI: 10.1017/s1751731119002611
|View full text |Cite
|
Sign up to set email alerts
|

Milk and meat fatty acids from sheep fed a plantain–chicory mixture or a grass-based permanent sward

Abstract: Plantain and chicory are interesting forage species since they present good nutritional quality and are more resistant to drought than many temperate grasses. The fatty acid (FA) profile in milk and meat is related to a growing concern for the consumption of healthy foods, that is, with a lower content of saturated FA, higher polyunsaturated FA (PUFA) and a favourable n-6 : n-3 FAs ratio. Our objective was to evaluate the FA content in ewe’s milk and lamb’s meat fed a plantain–chicory mixture (PCH) or a grass-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Numerous studies have evaluated the effect of these two contrasting feeding systems on meat flavor and their relationship with levels of fatty acid and volatile compounds [6][7][8][9]. Although the impact that different pasture-based production systems have on lamb meat fatty acid profiles has been characterized [10][11][12][13], less is known about its impact on eating quality. Lamb production in New Zealand is mainly based on grazing systems where various pasture combinations suit different environments across the country.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have evaluated the effect of these two contrasting feeding systems on meat flavor and their relationship with levels of fatty acid and volatile compounds [6][7][8][9]. Although the impact that different pasture-based production systems have on lamb meat fatty acid profiles has been characterized [10][11][12][13], less is known about its impact on eating quality. Lamb production in New Zealand is mainly based on grazing systems where various pasture combinations suit different environments across the country.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, botanically‐diverse pasture may contain plant secondary metabolites that can help reduce biohydrogenation of PUFA, which could explain the higher proportions of n ‐3 FA present in ruminant products from mountainous or species‐rich forage 38,40 . Studies confirm that herb species such as chicory contain condensed tannins, 41 whereas plantain is rich in phenolic and bioactive compounds such as acteoside and aucubin, which can inhibit microbial fermentation, resulting in a greater outflow of PUFA 42 . Plant secondary metabolites were not measured in this study, and so their presence in the pastures species can only be inferred.…”
Section: Discussionmentioning
confidence: 99%
“…38,40 Studies confirm that herb species such as chicory contain condensed tannins, 41 whereas plantain is rich in phenolic and bioactive compounds such as acteoside and aucubin, which can inhibit microbial fermentation, resulting in a greater outflow of PUFA. 42 Plant secondary metabolites were not measured in this study, and so their presence in the pastures species can only be inferred. Similar to this study, higher proportions of C18:3n-3c were reported in the muscle of steers grazing chicory compared to alfalfa, bermudagrass and pearl millet, 18 for which secondary metabolites could be partially responsible.…”
Section: Muscle Fasmentioning
confidence: 94%
“…This study was derived from the same swards and animals already published in Rodríguez et al [14] and Rodríguez et al [15].…”
Section: Methodsmentioning
confidence: 99%